PRESOWING SEED TREATMENT WITH THE CELL EXTRACTS AND CULTURE FILTRATES OF DIFFERENT ALGAE ON THE GROWTH AND DEVELOPMENT OF PEA SEEDLINGS - Kumar, Abhaya (Ecoprint: An International Journal of Ecology, 2004)
Algae have very short span of life but have high potency of multiplication and growth. During its growth, a great variety of substances like growth promoters as well as growth inhibitors are synthesized intracellularly and they are leached out in the surrounding medium. These substances have marked beneficial effect on the growth and development of different crops.In the present investigation effect of presowing seed treatment with the cell extracts and culture filterate of four algae viz. Scenedesmus bijugatus, Anacystis nidulans, Nostoc linckia and Westiellopsis prolifica have been studied with reference to the length of root and shoot of pea seedlings. It has been observed that the pea seedlings showed better growth and development than control in the cell extracts and culture filterates of all the algae. The effect of cell extracts and culture filterates may be ascribed to the presence of growth promoting substances in addition to other nitrogenous substances synthesized by the actively growing population and the deleterious effects due to some growth inhibitors produced by the algae or exhaust of metabolites in the latter stages of growth.Key words: Cell extracts, algae, Pisum sativum.Ecoprint Vol.11(1) 2004.